Endovascular treatment of a subclavian artery pseudoaneurysm in a patient with a pancoast tumor - Samuel J. Mouyal; Xavier Guerra; Tom Boeken; Alessandro Di Gaeta; Crina Bordeianu; Manuel Gargiulo; Olivier Pellerin; Marc Sapoval; Marc Al Ahmar (CVIR Endovascular)
Abstract Background The authors report herein a rare case of an endovascular management of a giant subclavian artery pseudoaneurysm, revealed by a massive hemoptysis in a patient suffering from a Pancoast tumor. Case presentation The endovascular procedure consisted of covering the subclavian artery rupture site with a stent graft after occluding the proximal segments of the ipsilateral internal thoracic and vertebral arteries. Conclusion Subclavian artery rupture was effectively managed using endovascular techniques via radial access.